DEVELOPMENT OF LEARNING MEDIA USING SCRATCH ON ELECTRICAL MEASURING INSTRUMENT MATERIAL TO IMPROVE STUDENT LEARNING OUTCOMES - Nur Rahmat, Taufiq Bayu; Perdana, Riki (PILLAR OF PHYSICS EDUCATION, 2023)
Physics learning media is very important to be used in learning to attract students' interest in teaching and learning activities. These learning media can be created using the help of 3D application Scratch. One of the materials that can be made using Scratch media is a voltmeter electric measuring instrument. Abstract physics material can be explained using the help of Scratch-assisted learning media. Therefore, a 3D application-assisted physics learning media was created on the topic of voltmeter electric measuring instruments to improve student learning outcomes. The purpose of this research is to develop Scratch-based physics learning media on the subject of voltmeter electric measuring instruments. In addition, this study also aims to determine the feasibility of Scratch-based physics learning media on the subject of voltmeter electric measuring instruments that have been made. The research was conducted with a 4D development model with stages in the form of define, planning stage, development stage, and dissemination stage. The analysis was performed using the SBi method by converting ordinal data to intervals using MSi analysis. The results showed that the learning media created was in the feasible category. Thus, learning media can be used in learning.